Energy crops on less favoured (alkaline) soil - Blaskó, Lajos; Czimbalmos, Róbert (Acta Agraria Debreceniensis, 2012)
The reduction in fossil energy and row material sources induces growing demand for renewable resources. The growing demand for herbal raw materials has land use impacts as well. One way to reduce the conflict between the food and energy crops can be the utilization of less favored areas by growing energy crops. Among the potentially available areas for this purpose the salt affected soils (SAS) occupy a significant territories. SAS with structural B-horizon (meadow solonetz soils) represent the most wide spread group of SAS in Hungary. About half of these soils have been reclaimed and used as arable land and the remaining 50% are used as grassland. Sweet sorghum production for manufacturing of alcohol production was investigated in a long term amelioration and fertilization experiment on a salt affected soil (meadow solonetz). By means of regression analyzes the effect of sodium content of the soil and increasing mineral fertilizer doses were studied. According to the multiple regression analysis only the effect of nitrogen fertilizer was significant. On the solonetz type salt affected soil the effect of water soluble salt content of the soil was not significant, but there was a closer correlation between the ammonium-lactate sodium content and the yield of sweet sorghum. The maximum green mass was 45–50 t ha-1, in the case of low Na content and high level of nitrogen fertilization.In order to quantify the potential yield of natural grass vegetation the relationship between the soil forming processes and the grass vegetationwas investigated. Beyond the different forms of Na-accumulation, the spatial pattern (mosaic-like characteristic) is also an inseparable feature of salt affected soils. The difference in the water regime, caused by the micro-relief is the main cause of variability. The run-on water keeps the deeper parts of the catena position wet longer. The wet situation causes more intensive leaching. In the low-laying parts of salt affected soils species preferring wet situations (mainly Alopecurus pratensis) are in majority. On the higher parts of the micro-relief species tolerating dry situations (mainly Festuca  pseudovina) are dominant. The yearly grass production of low laying areas can be 4–7 t ha-1 but because of prolonged wet  conditions the grass is not grazed and mowing can only be in old state. This old grass is not proper for feeding, but it may be suitable as energy plant.